Dancing the demons away dance movement therapy as a tool in counseling sexually abused children - Baraero, Dinghy Kristine M. (2005)
This research investigated the effects of Dance/Movement Therapy (DMT) as a therapeutic intervention among sexually abused girls who were institutionalized in a government shelter. Findings showed that it could be an effective tool in helping sexually abused children increase their body awareness, improve their body image and enhance self-esteem. The DMT sessions had a cathartic effect on girls since it helped them express through symbolic movement and imagery certain emotions that they may have otherwise presented.